Does involvement in food preparation track from adolescence to young adulthood and is it associated with better dietary quality? Findings from a ten-year longitudinal study - Laska, Melissa Nelson (2011)
OBJECTIVES: To examine whether involvement in food preparation tracks over time, between adolescence (15–18 years), emerging adulthood (19–23 years), and the mid-to-late twenties (24–28 years), as well as examine 10-year longitudinal associations between home food preparation, dietary quality and meal patterning. DESIGN: Population-based, longitudinal cohort study. SETTING: Participants were originally sampled from Minnesota public secondary schools (USA). SUBJECTS: Participants enrolled in Project EAT (Eating Among Teens)-I, EAT-II, and EAT-III (n=1,321). RESULTS: Most participants in their mid-to-late twenties reported an enjoyment of cooking (73% of males, 80% of females); however, few prepared meals including vegetables most days of the week (24% males, 41% females). Participants in their mid-to-late twenties who enjoyed cooking were more likely to have engaged in food preparation as adolescents and emerging adults (p<0.01); those who frequently prepared meals including vegetables were more likely to have engaged in food preparation as emerging adults (p<0.001), but not adolescents. Emerging adult food preparation predicted better dietary quality five years later in the mid-to-late twenties, including higher intakes of fruit, vegetables, dark green/orange vegetables, and less sugar sweetened beverage and fast food consumption. Associations between adolescent food preparation and later dietary quality yielded few significant results. CONCLUSIONS: Food preparation behaviors appeared to track over time, and engagement in food preparation during emerging adulthood, but not adolescence, was associated with healthier dietary intake during the mid-to-late twenties. Intervention studies are needed to understand whether promoting healthy food preparation results in improvements in eating patterns during the transition to adulthood.